2021
DOI: 10.18700/jnc.210016
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury in extracorporeal cardiopulmonary resuscitation: translational to clinical research

Abstract: The addition of extracorporeal membrane oxygenation (ECMO) to conventional cardiopulmonary resuscitation (CPR), termed extracorporeal cardiopulmonary resuscitation (ECPR), has significantly improved survival in selected patient populations. Despite this advancement, significant neurological impairment persists in approximately half of survivors. ECPR represents a potential advancement for patients who experience refractory cardiac arrest (CA) due to a reversible etiology and do not regain spontaneous circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 111 publications
(151 reference statements)
0
11
0
Order By: Relevance
“…Although cross-sectionally the ECMO pump ow rates were small and may not be clinically meaningful, over the duration of ECMO support these differences may accrue to substantial differences. While pre-ECMO cardiac arrest is a known risk factor for CNS ischemia in ECPR patients, (2,31) likely related to reperfusion injury and associated reactive oxygen species formation, (31,32) we also note that this factor was highly important in VV-ECMO patients (33) which has not been previously reported. These comparisons suggest there are similar underlying but overall divergent risk factors between these populations, which necessitates further investigation with prospective observational studies.…”
Section: Discussionmentioning
confidence: 60%
“…Although cross-sectionally the ECMO pump ow rates were small and may not be clinically meaningful, over the duration of ECMO support these differences may accrue to substantial differences. While pre-ECMO cardiac arrest is a known risk factor for CNS ischemia in ECPR patients, (2,31) likely related to reperfusion injury and associated reactive oxygen species formation, (31,32) we also note that this factor was highly important in VV-ECMO patients (33) which has not been previously reported. These comparisons suggest there are similar underlying but overall divergent risk factors between these populations, which necessitates further investigation with prospective observational studies.…”
Section: Discussionmentioning
confidence: 60%
“…This intricate procedure demands procedural expertise, teamwork, and meticulous monitoring to ensure optimal blood flow and prevent complications. ECPR is integrated within a continuum of care, encompassing postresuscitation management, cardiac catheterization to address underlying causes, targeted temperature management to mitigate brain injury, 55 and ongoing monitoring of cardiac function 56 and neurological status 57,58 . The collaborative efforts of healthcare professionals from various disciplines are fundamental to this system, allowing for swift and strategic decision‐making throughout each stage of care, ultimately increasing the potential for improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Induced by ECMO circuit, the absence of pulsatility is associated with reduced O 2 consumption and impaired cerebral autoregulation, potentially contributing to CNS ischemia. 21 Furthermore, low PP can indicate inadequate cardiac contractility, and thus systemic hypoperfusion, which may increase the risk of CNS ischemia. Interestingly, in contrast to previous literature describing that a larger delta PaCO 2 was associated with ICH, 42 our study demonstrated that delta PaCO 2 was associated with CNS ischemia rather than ICH.…”
Section: Discussionmentioning
confidence: 99%